Corruption in Schools, What’s the Matter ??? - Ismatullah, Ismet (Journal of Applied Business, Taxation and Economics Research, 2023)
Fraud can be committed by anyone because the main factor of fraud is human. A study conducted by Indonesia Corruption Watch on the trend of prosecution of corruption cases shows that the education sector is one of the sectors that is consistently the most corrupted sector. The large budget given to the education sector is one of the potential corruptions for irresponsible parties, even in the midst of the Covid-19 pandemic, corruption in the education sector has not stopped. This research is a literature review where researchers review literature related to this research. The results of this study are expected to provide benefits for related parties in preventing fraud in the world of education. Fraud prevention can be carried out by all parties with the aim of rejecting or understanding everything that can harm the company. In developing an effective fraud prevention strategy, organizations must pay attention to several things, including: 1) internal and external environmental conditions, 2) the complexity of business activities, 3) the potential, types and risks of fraud, 4) the adequacy of the resources needed.